Optimizing Media and Cyber Counseling for Generation Z in Schools: A Literature Review Study - Lestari, Widya; Miswati; Husaini, Muhammad Jawahir; Manurung, Afwan Syahril (Yayasan Amanah Nur Aman, 2024)
This article discusses the use of media & cyber counseling for the z generation. As is known, currently technological advances are developing very quickly so that the world of education must also follow the development of this technological progress. This era has entered the next era known as generation Z (gen Z), where this generation tends to be more accustomed to using internet technology and is proficient in using it in everyday life, in fact technology and the internet cannot be separated from the lives of generation Z. For this reason, counseling guidance seeks to keep up with current technology, namely by keeping up with current developments by utilizing media & cyber techniques in conducting counseling sessions. In this way, this technique can help generation Z who want to have counseling sessions anytime and anywhere.